The Role of Financial Sectors in the Financial System (Eurasian Journal of History, Geography and Economics, 2023)
This article covers the structure of the financial sector and the financial sector, and gives a short scientific definition of it. The priority directions of the strategy for the reforms and the improvement of the state financial system have been reflected.